Soreness during non-music activities is associated with playing-related musculoskeletal problems: an observational study of 731 child and adolescent intrumentalists - Ranelli, Sonia; Straker, Leon; Smith, Anne (Australian Physiotherapy Association, 2014)
Question: Is exposure to non-music-related activities associated with playing-related musculoskeletal problems in young instrumentalists? Is non-music-activity-related soreness associated with playing-related musculoskeletal problems in this group of instrumentalists? Design: Observational study using a questionnaire and physical measures. Participants: 859 instrumentalists aged 7 to 17 years from the School of Instrumental Music program. Results: Of the 731 respondents who completed the questionnaire adequately, 412 (56%) experienced instrument-playing problems; 219 (30%) had symptoms severe enough to interfere with normal playing. Children commonly reported moderate exposure to non-music-related activities, such as watching television (61%), vigorous physical activity (57%), writing (51%) and computer use (45%). Greater exposure to any non-music activity was not associated with playing problems, with odds ratios ranging from 1.01 (95% CI 0.7 to 1.5) for watching television to 2.08 (95% CI 0.5 to 3.3) for intensive hand activities. Four hundred and seventy eight (65%) children reported soreness related to non-music activities, such as vigorous physical activity (52%), writing (40%), computer use (28%), intensive hand activities (22%), electronic game use (17%) and watching television (15%). Non-music-activity-related soreness was significantly associated with instrument playing problems, adjusting for gender and age, with odds ratios ranging from 2.6 (95% CI 1.7 to 3.9) for soreness whilst watching television, to 4.3 (95% CI 2.6 to 7.1) for soreness during intensive hand activities.Conclusion: Non-music-activity-related soreness co-occurs significantly with playing problems in young instrumentalists. The finding of significant co-occurrence of music and non-music-related soreness in respondents in this study suggests that intervention targets for young instrumentalists could include risk factors previously identified in the general child and adolescent population, as well as music-specific risk factors. This is an important consideration for the assessment and management of the musculoskeletal health of young musicians.